Flavofun: Exploration of fungal flavoproteomes - Kerschbaumer, Bianca; Bijelic, Aleksandar; Macheroux, Peter (Frontiers in Catalysis, 2022)
Fungi produce a plethora of natural products exhibiting a fascinating diversity of chemical structures with an enormous potential for medical applications. Despite the importance of understanding the scope of natural products and their biosynthetic pathways, a systematic analysis of the involved enzymes has not been undertaken. In our previous studies, we examined the flavoprotein encoding gene pool in archaea, eubacteria, the yeast Saccharomyces cerevisiae, Arabidopsis thaliana and Homo sapiens. In the present survey, we have selected the model fungus Neurospora crassa as a starting point to investigate the flavoproteomes in the fungal kingdom. Our analysis showed that N. crassa harbors 201 flavoprotein-encoding genes amounting to 2% of the total protein-encoding genome. The majority of these flavoproteins (133) could be assigned to primary metabolism, termed the "core flavoproteome” with the remainder of flavoproteins (68) serving in, as yet unidentified, reactions. The latter group of "accessory flavoproteins" is dominated by monooxygenases, berberine bridge enzyme-like enzymes, and glucose-methanol-choline-oxidoreductases. Although the exact biochemical role of most of these enzymes remains undetermined, we propose that they are involved in activities closely associated with fungi, such as the degradation of lignocellulose, the biosynthesis of natural products and the detoxification of harmful compounds in the environment. Based on this assumption, we have analyzed the accessory flavoproteomes in the fungal kingdom using the MycoCosm database. This revealed large differences among fungal divisions, with Ascomycota, Basidiomycota and Mucoromycota featuring the highest average number of genes encoding accessory flavoproteins. Moreover, a more detailed analysis showed a massive accumulation of accessory flavoproteins in Sordariomycetes, Agaricomycetes, and Glomeromycotina. In our view, this indicates that these fungal classes are proliferative producers of natural products and also interesting sources for flavoproteins with potentially useful catalytic properties in biocatalytic applications.